Two novel phages infecting Erythrobacter isolated from the epipelagic ocean - Lu, Longfei; Huang, Xingyu; Zheng, Pengfei; Wei, Shuzhen; Jiao, Nianzhi; Zhang, Rui; Li, Xuejing; Yang, Yunlan (Frontiers in Microbiology, 2025)
Erythrobacter, an aerobic anoxygenic photoheterotrophic bacterial genus, plays a vital role in carbon and energy cycling in marine environments. However, their phage predators remain poorly understood, with only two strains previously reported. This study isolated and characterized a novel Erythrobacter phage, vB_EauS-R34L1 (R34L1), and its sub-strain vB_EauS-R34L2 (R34L2), from coastal seawater. Both phages exhibit long-tailed, icosahedral morphologies and relatively narrow but slightly different host ranges. One-step growth curve analysis revealed a 160-min latent period and burst sizes of 81 and 91 PFU/cell for R34L1 and R34L2, respectively. Genomic analysis showed that the phages possess dsDNA genomes of 56,415 bp (R34L1) and 54,924 bp (R34L2), with G + C contents of 61.60 and 61.19%, respectively. Both phages harbor a suite of unique genes, including GapR and GH19, which are crucial for host interaction and ecological functionality. Blastn analysis indicated a 99.73% genome similarity between them. Taxonomic and phylogenetic analyses positioned them in a novel viral genus cluster, Eausmariqdvirus, under the family Casjensviridae, indicating a distant evolutionary relationship with known phages. Metagenomic queries suggested that R34L1- and R34L2-like phages are exclusively abundant in temperate and tropical epipelagic zones. This study expands our understanding of Erythrobacter phages and provides insights into their ecological roles in marine ecosystems.